First case of fungal peritonitis caused by Neosartorya hiratsukae in China - Kaixuan Yuan; Xiaoxiao Wang; Yong Ling; Ye Long; Zhuoxi Chen; Yunhu Zhao (Medical Mycology Case Reports)
Fungal peritonitis, an uncommon complication in continuous ambulatory peritoneal dialysis (CAPD), has recently garnered increased attention due to its incidence and potential mortality. To the best of our knowledge, this is the first confirmed case of Neosartorya hiratsukae (N. hiratsukae) causing CAPD-related peritonitis in a patient with chronic nephrotic syndrome in Guangzhou, China. After prompt removal of the peritoneal catheter and active antifungal therapy, no clinical manifestations of peritonitis were observed. Our report underscores the importance of enhancing clinical awareness regarding N. hiratsukae and ensuring timely diagnosis in cases of CAPD-related fungal peritonitis.